Investor reactions to climate change disclosures: Joint effects of disclosure focus and controllability - Phang, Soon‐Yeow; Dharmasiri, Prabashi; Puspitasari, Dani (Contemporary Accounting Research, 2025)
Abstract When evaluating the potential financial effects of climate change, investors demand disclosures of the climate‐related risks and opportunities that companies need to manage. We examine how and why management control over climate change performance affects investors' evaluations of such disclosures. In a series of experiments, we find that investors believe that managerial optimism is beneficial and, thus, are more willing to invest when climate‐related disclosures focus on opportunities rather than risks. This effect, however, occurs only when management has high control over the company's future climate change performance. When that control is low, investors believe that managerial realism is beneficial and, thus, are more willing to invest when these disclosures focus on risks rather than opportunities. Our study has implications for companies and standard setters considering the consequences of focusing on either risks or opportunities in climate change reporting and the conditions under which one focus or the other may be beneficial.